Governing Universities in Post-Soviet Countries - Eckel, Peter D. (Cambridge University Press, 2024)
Leveraging the natural experiment caused by the dissolution of the USSR and its uniform approach to higher education, this book focuses on university governance across the former Soviet countries, making it essential reading for researchers, students and policy makers. This title is also available as open access on Cambridge Core.